To solve, simply layout an equation.
(2x+3)(x+4)=1
Step 1: Simplify both sides of the equation.
2x2+11x+12=1
Step 2: Subtract 1 from both sides.
2x2+11x+12−1=1−1
2x2+11x+11=0
Step 3: Use quadratic formula with a=2, b=11, c=11.
x=-b±√b^2-4ac/2a
So, the answer for this problem is:
x=-11/4+1/4√33 or -11/4+-1/4√33
It's D $68.52 due to the act that 42.18 + 26.34= $68.52
Answer:
15
Step-by-step explanation:
The hypotenuse of a triangle is a² + b² = c².
12² + 9² = c²
144 + 81 = 225
√225 = 15
The answer for number A would be 1/3